Contrasting evolution of iron phase composition in soils exposed to redox fluctuations. (15th August 2018) - Winkler, Pauline; Kaiser, Klaus; Thompson, Aaron; Kalbitz, Karsten; Fiedler, Sabine; Jahn, Reinhold
Abstract: Ferric iron (Fe III ) solid phases serve many functions in soils and sediments, which include providing sorption sites for soil organic matter, nutrients, and pollutants. The reactivity of Fe solid phases depends on the mineral structure, including the overall crystallinity. In redox-active soils and sediments, repeated reductive dissolution with subsequent exposure to aqueous ferrous iron (Fe 2+ ) and oxidative re-precipitation can alter Fe phase crystallinity and reactivity. However, the trajectory of Fe mineral transformation under redox fluctuations is unclear and has been reported to result in both increases and decreases in Fe phase crystallinity. Several factors such as water budget, organic matter input, redox dynamics as well as the initial Fe phase composition might play a role. The objective of our study was to examine if Fe minerals in soils that differ in porosity-dependent water leaching rate and initial Fe phase crystallinity, demonstrate distinct mineral transformations when subjected to redox fluctuations. We sampled paired plots of two soil types under similar management but with different water leaching rates and contrasting Fe oxide crystallinity — an Alisol rich in crystalline Fe phases and an Andosol rich in short-range-ordered (SRO) Fe phases. The two soils were either exposed to several decades of redox fluctuations during rice paddy cultivation (paddy) or to predominantly oxic conditions in neighboring vegetable gardens (non-paddy). Paddy soils are uniquely suited for this type of study because they are regularly submerged and develop regular redox fluctuations. We also incubated the non-paddy soils in the laboratory for one year through eight anoxic/oxic cycles and monitored the aqueous soil geochemistry. Mössbauer spectroscopy was then used to evaluate Fe mineral speciation in field soils (paddy and non-paddy) and laboratory incubations. In the field soils, we found that redox fluctuation had contrasting effects on Fe oxide crystallinity, with crystallinity being lower in the Alisol paddy soil and higher in the Andosol paddy soil than in their corresponding non-paddy controls. In the laboratory incubation experiment, Eh, pH and dissolved Fe 2+ responded as anticipated, with elevated Fe 2+ concentrations during the anoxic periods as well as low Eh and high pH. Mössbauer measurements suggest the fluctuating redox incubation was beginning to alter Fe oxide crystallinity along the same trajectory as observed in the field, but the changes were within the range of fitting errors. We propose that reductive dissolution of crystalline Fe oxides prevails in the soil rich in crystalline Fe oxides (Alisol) and that re-precipitation as SRO Fe oxides is favored by constrained leaching, which leads to the observed decrease in Fe oxide crystallinity. In the soil rich in SRO Fe phases (Andosol), preferential reductive dissolution of SRO Fe oxides coupled with stronger leaching of dissolved Fe 2+ causes the observed relative increase in crystallinity of the remaining Fe oxides. The observed increase in Fe oxide crystallinity may further be a result of Fe(II)-catalyzed re-crystallization of SRO Fe oxides. These findings indicate that, besides other factors, the Fe mineral composition of the initial soil or sediment as well as the leaching rate likely influence the trajectory of Fe oxide evolution under alternating redox-conditions.